2014
DOI: 10.7589/2013-07-183
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced Rabies in a Red Fox (Vulpes vulpes): Isolation of Vaccine Virus in Brain Tissue and Salivary Glands

Abstract: ABSTRACT:Oral vaccination campaigns to eliminate fox rabies were initiated in Slovenia in 1995. In May 2012, a young fox (Vulpes vulpes) with typical rabies signs was captured. Its brain and salivary gland tissues were found to contain vaccine strain SAD B19. The Basic Logical Alignment Search Tool alignment of 589 nucleotides determined from the N gene of the virus isolated from the brain and salivary glands of the affected fox was 100% identical to the GenBank reference SAD B19 strain. Sequence analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Strikingly, in contrast to the ERA vaccine-induced rabies cases, for the SAD Bern orig -induced rabies cases no SNVs already present in the progenitor vaccines were selected, even though a higher number of variants were detected in the SAD Bern orig -derived vaccine virus strain (N mean ≈ 47, see Table S8, Supplementary File) than in the ERA-BHK21 strain (N = 31, see Figure 2 and Table S7). Also, the consensus sequences of viruses from the SAD Bern orig vaccine-induced rabies cases showed a high sequence identity to their progenitor vaccine virus strain at the consensus level, ranging from zero to four nucleotide exchanges, confirming previous studies [13,15,18].…”
Section: Sad Bern Orig -Derived Cases Are Defined By High Sequence Idsupporting
confidence: 87%
See 1 more Smart Citation
“…Strikingly, in contrast to the ERA vaccine-induced rabies cases, for the SAD Bern orig -induced rabies cases no SNVs already present in the progenitor vaccines were selected, even though a higher number of variants were detected in the SAD Bern orig -derived vaccine virus strain (N mean ≈ 47, see Table S8, Supplementary File) than in the ERA-BHK21 strain (N = 31, see Figure 2 and Table S7). Also, the consensus sequences of viruses from the SAD Bern orig vaccine-induced rabies cases showed a high sequence identity to their progenitor vaccine virus strain at the consensus level, ranging from zero to four nucleotide exchanges, confirming previous studies [13,15,18].…”
Section: Sad Bern Orig -Derived Cases Are Defined By High Sequence Idsupporting
confidence: 87%
“…Although various studies have focused on oral rabies vaccine-induced cases [1,7,13,18,33], only a few studies have comprehensively investigated those cases and their progenitor vaccine viruses at a population level [14,15]. The latter showed a high genetic heterogeneity in different vaccine virus strains as opposed to viruses from vaccine-induced rabies cases, indicating a substantial loss in viral population diversity.…”
Section: Discussionmentioning
confidence: 99%
“…One is Rabigen SAG2™, produced by Virbac SA, France (101), and the other is Raboral V-RG ® , produced by Merial Inc., USA (102). The other commercial vaccines have residual virulence that can induce rabies, in target and non-target species (103, 104). …”
Section: Resultsmentioning
confidence: 99%
“…Salivary glands of positive foxes were not investigated. More recently, a paper demonstrated that a vaccineassociated virus might have been present in the brain tissue and also in the salivary glands of a naturally infected fox in an area vaccinated with the SAD B19 vaccine in Slovenia (Hostnik et al, 2014). Only one animal was tested for salivary excretion and was negative.…”
Section: Safetymentioning
confidence: 99%